2017
DOI: 10.1002/admi.201700043
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition Enabled Perovskite/PEDOT Solar Cells in a Regular n–i–p Architectural Design

Abstract: Perovskite solar cells employing poly(3,4‐ethylenedioxythiophene) (PEDOT) as hole transport layer on top of methylammonium lead halide are reported, yielding a power conversion efficiency of 11% and a 6% stabilized power output. An atomic layer deposition assisted interface architectural approach is adopted to fabricate the n–i–p perovskite/PEDOT devices. The results present a promising next step toward efficient low‐cost perovskite‐based photovoltaic technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 70 publications
1
26
1
Order By: Relevance
“…These values fall in the range of the HTM thicknesses (40–300 nm) employed in the case of MAPbI 3 PSCs using PEDOT. 21,22 Raman-spectroscopic studies (Figure 2D) further confirmed the characteristics of an electrochemically deposited PEDOT on top of the MAPbI 3 layer.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…These values fall in the range of the HTM thicknesses (40–300 nm) employed in the case of MAPbI 3 PSCs using PEDOT. 21,22 Raman-spectroscopic studies (Figure 2D) further confirmed the characteristics of an electrochemically deposited PEDOT on top of the MAPbI 3 layer.…”
Section: Resultsmentioning
confidence: 54%
“…Although it was demonstrated that PEDOT accepts holes as effectively as spiro-OMeTAD, 20 its use apart from a few examples, 2123 has been restricted to inverted SC designs ( p–i–n junction). The direct spin-coating of the aqueous PEDOT:PSS solution is not a good option because it is known to degrade the perovskite layer.…”
mentioning
confidence: 99%
“…These values fall in the range of the HTM thicknesses employed in the case of MAPbI3 solar cells using PEDOT. [194,195] Raman-spectroscopic studies ( Figure 53D) further confirmed the presence of a PEDOT layer on the surface of the PSCs.…”
Section: Morphological Features Of Electrodeposited Pedotmentioning
confidence: 69%
“…Although it was demonstrated that PEDOT accepts holes as effectively as spiro-MeOTAD, [193] its use (apart from a few examples [194][195][196] ) has been restricted to inverted solar cell designs (p-i-n junction). This limit is rooted in the fact that the direct spin-coating of the PEDOT:PSS aqueous solutions would immediately destroy the perovskite layer.…”
Section: Conducting Polymers As Hole Transporters In Perovskite Solarmentioning
confidence: 99%
See 1 more Smart Citation